Pengaruh Pemberian Pupuk Hayati dan SP-36 untuk Meningkatkan Hasil Tomat (Solanum lycopersicum L.) pada Tanah Gambut Pedalaman - Mendang J Sinaga; Titin Apung Atikah; Siti Zubaidah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
This study aims to determine the effect of biological fertilizers and SP 36 on tomato yields on inland peat soils and determine the best concentration of biological fertilizers and doses of SP-36 that can increase tomato yields. This research took place at the Installation of Experimental Garden of Agriculture, Faculty of Agriculture, University of Palangka Raya. The design used in this study was a factorial Completely Randomized Design (CRD) and was repeated 3 (three) replications. The first factor was the concentration of biological fertilizers (H) which consist 4 levels: H0= 0 ml.-1; H1= 2 ml.l-1; H2= 5 ml.l-1; H3= 7 ml.l-1. The second factor was the dose of SP-36 (P) which consist 3 levels: P1=150 kg.ha-1(5,11 g.polybag-1); P2= 200 kg.ha-1 (6,81 g.polybag-1); P3=250 kg.ha-1 (8,52 g.polybag-1). The results showed that the combination of biological fertilizers and SP-36 did not interact with all observed variables. Biofertilizer dose 7 ml.l-1 showed the best result of the number of fruits were 15.67 fruits, the weight of fresh fruits were 220.16 g, and the dry weight of tomatoes root were 9.92 g. SP-36 fertilizer dose 200 kg.ha-1 showed the best result of the number of fruits were 16.42 fruits, the weight of fresh fruit of tomatoes were 232.51 g, the weight of fresh root were 26.93 g and the weight of dry root were 9.38 g.